Structural, optical and magnetic properties of YIG and TbErIG nanofilms prepared using a sol-gel method. (April 2019) - Elhamali, Suleiman M.; Ibrahim, N.B.; Radiman, S.
Graphical abstract: Highlights: The pure phase of YIG and TbErIG films was prepared using a sol-gel method. The effects of crystallisation within various annealing environments (air, oxygen and argon atmospheres) were investigated. The IR spectra of the TbErIG films confirmed the formation of a garnet structure. The film transparency of YIG films was improved with co-doping in the visible and near-infrared regions. The magnetic properties were investigated using a vibrating sample magnetometer (VSM) for the in-plane M(H∥), out-plane M(H⊥) and temperature dependence curves (M-T). Abstract: A series of yttrium iron garnet (YIG) and terbium erbium iron garnet (TbErIG) nanocrystalline films was successfully grown using a sol-gel method. A crystalline analysis carried out using an X-ray diffractometer confirmed that all films had a single-phase garnet structure. The TbErIG films annealed in O2 and Ar gas had a larger number of crystallisation peaks, with a lattice constant that was close to the standard value for ErIG. The transparency increased from 94% for YIG (O2 ) to 98% for TbErIG (O2 ) films in the near-infrared region. All films were soft ferrite materials, as indicated by their magnetic hysteresis loops. The value of saturated magnetisation was increased for samples annealed in air, and was markedly decreased for samples subjected to O2 and Ar atmospheres. An increase in the coercivity value (91 Oe) was also observed for the TbErIG (Ar) film. YIG and TbErIG showed a phase transition from ferrimagnetic to paramagnetic at the Curie temperature, Tc  = 556 K and 557.3 K, respectively. The low saturation magnetisation, low optical absorption and highly crystalline structure of TbErIG (O2 and Ar) films mean that these films may potentially be used in a magneto-optical compact isolator in the visible and NIR regions.